Penyuluhan Bahaya Penipuan Online sebagai Bentuk Peningkatan Literasi Digital bagi Masyarakat - Winarno; Yudin Joko Prasojo; Maulana Malik Ibrahim; Tesalonika Ajeng Joanida; Nanda Saskya; Janeayun Irgarenata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Fraud is a crime committed for the benefit of one party or oneself at the expense of another party. With the development of the digital age, fraud can be carried out online as fraud today knows no boundaries of time and place. Bago Village is one of the remote villages in Slagen District that needs to improve its digital literacy. This is evidenced by the continued online fraud in the Bago village area. To avoid these problems, a digital competence consultation can be conducted. The purpose of this advice is to avoid online scams, use electronic devices more cautiously, and improve your digital prowess when dealing with social media. As a method, after socialization, the participants are measured by a questionnaire, and the counseling method is used to evaluate the results. The survey revealed that almost everyone in Bagor Village, Miri and Slagen use social media in their daily lives. In addition, 93.94% of the counseling participants were satisfied with their counseling activities regarding online fraud and improved their digital literacy knowledge to always be cautious when using social media. Finally, 95.45% of the participants hoped that such activities would be held regularly due to the rapid development of technology. This indicates that the expansion measures have been successfully implemented and have had a positive effect.